Factors influencing street-vended foods quality and safety in developing countries: a review - O. A. Bassitou Koumassa; Romaric Ouétchéhou; Mathias Hounsou; Oscar Zannou; D. Sylvain Dabadé (Discover Food)
Abstract Street foods are an economic activity and source of income for the poor while contributing to the population’s food and nutritional security. However, they are among the main transmission routes for foodborne diseases. This study aimed at carrying out an in-depth analysis of street foods in developing countries, focusing on factors affecting their quality and safety. To achieve this goal, a literature search was carried out on various databases, namely PubMed, Scopus, and Google Scholar, focusing on articles published on specific aspects of street food in developing countries. The results indicated that the primary factors influencing the quality and safety of street foods in several developing countries include the knowledge and hygiene practices of street food vendors, the sources of raw materials, packaging and storage practices, and the preparation or sales environment. Bacteria such as Escherichia coli, Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, and Salmonella spp. as well as heavy metals, polycyclic aromatic hydrocarbons, hair, and plastics were the hazards most commonly identified in street foods in developing countries. Moreover, regulations and policies relating to the sale of street foods are inadequately enforced in some developing countries and non-existent in others. To improve street food safety in developing countries, future research should extend beyond hazard identification to assess risks associated with street food consumption and identify effective interventions for risk management. With concerted efforts, sustained commitment, and behavioral changes from all stakeholders, the availability of safe street food for everyone could be ensured.